Desain dan Implementasi Kapasitor Bank Otomatis Berbasis Mikrokontroler untuk Koreksi Faktor Daya - Ibrohim; Subuh Isnur Haryudo; Endryansyah; Hafidz Nindhom Zen (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2026)
Electrical energy efficiency in household installations is a critical issue, primarily due to the low power factor (cos φ) caused by the dominant use of inductive appliances such as air conditioners, refrigerators, and water pumps. This condition results in significant energy losses and increases the load on residential electrical networks. This study designs an automatic capacitor bank system based on an Arduino Nano microcontroller to dynamically correct the power factor. The system is equipped with a PZEM-004T sensor to monitor voltage, current, and power factor in real time. Based on the measured data, the microcontroller automatically controls relay modules to connect capacitors with the most suitable capacitance according to load variations. The main innovation of this system lies in its adaptive automation mechanism, which enables a rapid and efficient response to electrical load fluctuations. Implementation results show that the system can improve the power factor to nearly 1.0, effectively reducing reactive energy consumption, lowering electricity costs, and enhancing the overall efficiency and stability of household electrical systems.